The Societal Relevance of the “Rheinischer Merkur” - Frey, Regina M. (Warszawskie Studia Teologiczne, 2021)
At present, there is no societally relevant political newspaper in Germany that is based on a Christian worldview. The Rheinischer Merkur, founded in 1946 shortly after the end of the Second World War and shut down by the German Bishops’ Conference in 2010, was a newspaper of this kind. It went beyond the Christian milieu in the fulfilment of its mission in the public arena. The closure of the Rheinischer Merkur obscures even today the decisive role it played in the elaboration of the Constitution of the Federal Republic of Germany and the substantial quality of the paper. This essay sketches the history of the Rheinischer Merkur and its self-understanding, as well as its decline, locating these in the context of the journalistic autonomies and media-ethical tensions to which every journalistic medium is subject.